Santal religiosity and the Christianization impact of conversion: A comparative situational viewpoint in regards to Orang Asli in Malaysia - Karim, A.H.M Zehadul; Awang, Yahya (2017)
Santals, the largest aboriginal group of people in Bangladesh, living in the north-western part of the country, are absolutely dependent on their traditional belief system with strict adherence to sanatoni (traditional) religious practices. Most recently, a large number of them have been converted to Christianity and are seemingly being formalized to a newly-evolved maladaptive religiosity. Historically speaking, the Santals arrived in Bangladesh during the British colonial period after they were driven out from the Indian Territory as they revolted against the British in 1855. To escape from their torturous persecution, they fled to move to Bangladesh settling mostly in the northern part of the country. Since then, they have been maintaining their own sanatani practices very comfortably without having any socio-political interference from their larger Bengali community. But as time passes by, in the last few decades, they have become the victims of the newly-emerged Bengali land grabbers, who pauperize them to extreme poverty and finally, almost exterminating them from their own settlement. As a consequence, a large group of Santals have now accepted Christianity and most of them have migrated to the peri-urban city centers seeking employment in different Christian-based professional organizations who support them economically. It will be however, unjust to say that the Christian missionaries forced them to such conversion; rather, it is their magnanimity and acceptability which attracted the adibashis to such conversion. It is learned that the missionary people are well-behaved, sociable and most frequently show extra modesty to everyone who eventually become attracted to them. By contrast, the Bengali mainlanders in fact, simply fail to integrate the Santals in their social interactions; rather they always keep a social distance, alienating the adibashis and arguing that they did not like the Santals for they drink alcohol. They do not consider the fact that drinking alcohol is part of their religious and cultural festivals. Due to such attitudinal distance, Bengali mainlanders and the Santal communities have never had any symbiotic relationship between them; instead, a kind of diametrically opposing sentiments have prevailed between these two groups of people which has a negative impact on human relationship.